2015
DOI: 10.1002/jmri.25097
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Bernoulli's method significantly underestimates pulmonary transvalvular pressure drop

Abstract: Purpose: To determine whether neglecting the flow unsteadiness in simplified Bernoulli's equation significantly affects the pulmonary transvalvular pressure drop estimation. Materials and Methods: 3.0T magnetic resonance imaging (MRI) 4D velocity mapping was performed on four healthy volunteers, seven patients with repaired tetralogy of Fallot, and thirteen patients with transposition of the great arteries repaired by arterial switch. Pulmonary transvalvular pressure drop was estimated based on two methods: Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Therefore, the true pressure drop and the predicted pressure drop, based on the simplified Bernoulli method are not directly interchangeable. The discrepancy between the simplified Bernoulli estimation and the true pressure drop has frequently been reported . Therefore, it functions as a relative metric for clinical cut‐off rather than a true pressure prediction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the true pressure drop and the predicted pressure drop, based on the simplified Bernoulli method are not directly interchangeable. The discrepancy between the simplified Bernoulli estimation and the true pressure drop has frequently been reported . Therefore, it functions as a relative metric for clinical cut‐off rather than a true pressure prediction .…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the simplified Bernoulli estimation and the true pressure drop has frequently been reported. [5][6][7][8]11 Therefore, it functions as a relative metric for clinical cut-off rather than a true pressure prediction. 33 Considering the significant amount of clinical data that have been obtained with the simplified Bernoulli method, further methods to make the various pressure estimations interchangeable would be an important issue to investigate in the future.…”
Section: F I G U R E 5 Comparison Of 4d Flow Mri Pressure Drop Estimamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the assumption of inviscid flow and the ideal energy conversion between kinetic energy and pressure, the simplified Bernoulli equation can overestimate the true irreversible pressure loss by neglecting pressure recovery in the post-stenotic region9. In addition, it can underestimate the true pressure difference by not accounting for flow unsteadiness, such as acceleration of the blood flow10. Several studies have proposed modified versions of the simplified Bernoulli equation by adding corrective terms.…”
mentioning
confidence: 99%
“…For example, the inclusion of a ratio between the effective aortic orifice area (EOA) and the aortic cross-sectional area to the simplified Bernoulli equation was presented based on the concept of fluid-dynamic energy loss through a sudden expansion, and it has shown the potential to reflect the pressure recovery in the post-stenosis region11. Parallel research on the Generalized Bernoulli equation suggested that the accuracy of the pressure drop estimation can be improved by including an acceleration term along a flow streamline upstream and downstream of the stenotic vessel10. However, the accuracy of the irreversible pressure drop estimation based on the Bernoulli equation in various pathological conditions remains uncertain12131415.…”
mentioning
confidence: 99%